The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1677/joe.0.1570305
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of the rat adrenal zona glomerulosa

Abstract: Using histochemical and immunocytochemical methods, cholinergic nerve fibres were demonstrated in the rat adrenal cortex, primarily in the capsule and zona glomerulosa, and in the medulla. Some terminated among the glomerulosa cells or around blood vessels. Occasional fibres were also seen in the fasciculata, ending in islets of chromaffin tissue without ramifications on cortical cells.To clarify the role of cholinergic innervation, a microvolume perifusion system was used to study steroid production by the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Previously we reported the presence of an extended peripheral cholinergic network in the zona glomerulosa of rat adrenal cortex (Jánossy et al, 1998). Cholinergic nerve fibres terminating in this area are the physiological source of OLF secretagogue, and ACh released from the nerve endings exerts a direct neuronal modulation on steroidogenesis in ZG cells.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previously we reported the presence of an extended peripheral cholinergic network in the zona glomerulosa of rat adrenal cortex (Jánossy et al, 1998). Cholinergic nerve fibres terminating in this area are the physiological source of OLF secretagogue, and ACh released from the nerve endings exerts a direct neuronal modulation on steroidogenesis in ZG cells.…”
Section: Discussionmentioning
confidence: 89%
“…Cholinergic nerve fibres terminating in this area are the physiological source of OLF secretagogue, and ACh released from the nerve endings exerts a direct neuronal modulation on steroidogenesis in ZG cells. For example, muscarinic regulation of cortisol and aldosterone, both in bovine adrenocortical cells (Benyamina et al, 1987;Kojima et al, 1986;Rubin and Warner, 1975) and in perfusion of rat adrenal capsule-glomerulosa preparations (Jánossy et al, 1998), has been reported. Nicotinic modulation of steroidogenesis in cat and rat adrenocortical cells (Skowronski and Feldman, 1994;Barbieri et al, 1989) and the influence of nicotine on the secretion of other steroids has also been reported (Skowronski and Feldman, 1994;Kasson and Hsueh, 1985;Patterson et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adrenal medulla receives a most dense nerve supply terminating on the postganglionic neurons and chromaffin cells (Kondo et al, 1985;Kesse et al, 1988). However, the adrenal cortex is also innervated, especially in the outer capsule and z. glomerulosa region (Watanabe et al, 1990;Janossy et al, 1998). Medullary neurons in the mammalian adrenal gland have been shown not only to innervate medullary chromaffin cells, but also to project to the cortex, approaching secretory cells and blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cholinergic nerve fibers in the adrenal glands has been studied in rat (Purwar, 1978;Parker et al, 1993;Janossy et al, 1998;Murabayashi et al, 2009), mouse (Oomori et al, 2013), guinea pig (Parker et al, 1990), cow (De Diego, 2010, goat (Watanabe et al, 1990), pig (Tornøe et al, 2000), and human (Charlton et al, 1991) using different markers. Additionally the vagal innervation of the adrenal gland of guinea pig and rat (Coupland et al, 1989;Tomlinson and Coupland, 1990) and the observation of AChE-positive neurons of rat adrenal medulla (Coupland and Holmes, 1958;Coupland, 1965a;Tomlinson and Coupland, 1990) support the localization of cholinergic nerve fibers in the adrenal glands.…”
Section: Introductionmentioning
confidence: 99%